Desain Sistem Monitoring Dan Kontrol Mobile Incinerator Berbasis Iot - Pratama, Ridho Adjie; Sumaryo , Sony; Permana, Agus Ganda (eProceedings of Engineering, 2024)
Incinerator is a tool used to burn waste that uses a furnace as a combustion chamber with a high temperature. The use of incinerators can be a solution to reduce waste. However, the use of incinerators must be closely monitored because the use of inappropriate incinerators can produce smoke containing harmful chemical compounds. Incinerator engine performance can be improved by using MQ-7, MQ-135 and MQ-136 sensors. Then to increase the level of effectiveness at the time of combustion can use Thermocouple to monitor the temperature in the combustion chamber in realtime. The use of a water boiler in the combustion chamber can increase the level of effectiveness during combustion because it can help increase the temperature in the combustion chamber and the use of Ultrasonic sensors to monitor the availability of water during combustion. Then to improve the performance of this incinerator machine can be controlled and monitored directly using a smartphone. In this research, the use of these sensors aims to determine whether the smoke produced by the incinerator is safe or not. The MQ-7 sensor can detect CO compounds. The MQ-135 sensor can detect CO2 and NOx compounds. Then the MQ-136 sensor can detect SO2 compounds. Then the use of Thermocouple in the combustion chamber can detect the temperature in the combustion chamber up to 1200 C. Keywords- Incinerator, Waste, Sensor, IoT